The Impact of Corporate Social Responsibility, Investment Decisions, and Profitability on Firm Value (Empirical Study on Consumer Non-Cyclicals Sector Companies Listed on The Indonesia Stock Exchange in 2021–2023) - Ni Komang Putri Seroja; Gede Juliarsa (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Firm value is the investors’ perception of a company's success in maximizing shareholder wealth, which is reflected through its stock price. The purpose of this study is to examine the effect of corporate social responsibility (CSR), investment decisions, and profitability on firm value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, with leverage as a control variable. This study employs a quantitative approach with an associative research design. The sample consists of 20 companies selected using purposive sampling, resulting in a total of 60 observations over three years. The analysis technique used is multiple linear regression with the assistance of SPSS software. The results show that CSR and profitability have a positive affect on firm value, while investment decisions do not have an affect. This study implies that companies need to enhance CSR practices and profitability to improve their firm value in the eyes of investors. Additionally, this study contributes theoretically to the development of literature on the factors influencing firm value and can serve as a reference for future research.